Determinants of Financial Information Quality in Aceh Government - Chudri, Intan Rizkia; Fitri, Aida; Delly, Hafifa (Penerbit Goodwood, 2026)
Purpose: This study aims to explore the effect of the Whistleblowing System (WBS) and External Pressure on the quality of financial information in government institutions, specifically focusing on Aceh Government Work Units (SKPAs). Methodology: A quantitative approach was employed, surveying 66 financial management staff members from various SKPAs in Aceh. The data was analyzed using multiple linear regression through SPSS software to assess the impact of WBS and External Pressure on financial information quality. Result: The study found that both WBS and External Pressure have significant positive effects on improving the quality of financial information. These two factors together explained 47.5% of the variance in financial information quality, with WBS having a slightly stronger impact compared to External Pressure. Conclusion: The research suggests that a robust Whistleblowing System and appropriate external pressure mechanisms are crucial for improving the transparency and accuracy of financial reporting within public sector institutions in Aceh. These findings underscore the importance of governance structures in enhancing financial integrity. Limitations: The study is limited by its focus on a single province and a cross-sectional research design, which limits its ability to generalize results and draw causal inference. Contribution: This study contributes to the literature on public sector governance by providing valuable insights into the role of internal and external control mechanisms in enhancing financial transparency in regions with special autonomy.